Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening Di Bank BNI - Nazli Ramadhani Lubis; Sonya Putri; Parapat Gultom (Jurnal Penelitian Ekonomi Akuntansi, 2024)
This study aims to analyze employee performance at Bank BNI by using work environment variables and compensation as independent variables and work motivation as an intervening variable to analyze the effect of employee motivation levels. The sampling technique of this study used purposive sampling which amounted to 100 employees. Data collected using a questionnaire method through Google Form. The data analysis technique in this study was carried out using SmartPLS. The results showed that the work environment has no significant effect on employee performance while compensation and motivation have a significant effect on employee performance. In addition, the work environment has a significant effect on work motivation but compensation has no significant effect on work motivation. The work environment has no significant effect on employee performance through work motivation. However, compensation has a significant effect on employee performance through work motivation. The limitation of this research is that it only uses BNI BANK and with limited respondents. Further research is recommended to expand the research area by using several BANKs and also adding respondents and other variables related to employee performance so that it will produce even better research.